Knowledge of non-communicable diseases and access to healthcare services among adults before and during COVID-19 pandemic in rural Tanzania - Nathanael Sirili; Manase Kilonzi; George Kiwango; Edward Lengai; Ramla Nandala; Dorkasi L. Mwakawanga; Erick G. Philipo; Joseph Matobo Thobias; Gasto Frumence (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic significantly affected access to healthcare services, particularly among individuals living with Non-Communicable Diseases (NCDs) who require regular healthcare visits. Studies suggest that knowledge about a specific disease is closely linked to the ability to access services for that condition. In preparation for the future, we conducted the study to assess knowledge of NCDs and access to healthcare services among adults residing in rural areas before and during the COVID-19 pandemic.MethodsWe conducted a community-based cross-sectional study in rural Tanzania in October 2022, a few months after the end of the third wave of the COVID-19 pandemic. A total of 689 community residents participated in the study. The level of knowledge of NCDs was assessed using an 11-item Likert questionnaire, which was later dichotomized into adequate and inadequate levels of knowledge. In addition, access to healthcare was assessed before and during the pandemic. We summarized the results using descriptive statistics and logistic regression was applied to determine factors associated with adequate levels of knowledge of NCDs. All statistical tests were two-sided; a p-value <0.05 was considered statistically significant. All data analyses were performed using SPSS.ResultsAmong 689 participants, more than half 369 (55%) had adequate knowledge of whether a disease is NCD or not; specifically, 495 (73.8%), 465 (69.3%), and 349 (52%) knew that hypertension, diabetes mellitus, and stroke are NCDs while 424 (63.2%) know that UTI is not NCD. Of the interviewed participants, 75 (11.2%) had at least one NCD. During the COVID-19 pandemic the majority 57 (72.2%) accessed healthcare services from nearby health facilities followed by traditional healers 10 (12.7%) and community drug outlets 8 (10.1%). Residence and education level were found to be significantly associated with knowledge of NCDs among participants.ConclusionThe study revealed that the community has a moderate level of knowledge of NCDs, and during the COVID-19 pandemic outbreaks, people living with NCD (s) relied on nearby health facilities to obtain healthcare services. Health system preparedness and response to pandemics should take into account empowering the community members to understand that NCD care is continuously needed even during pandemic times. We further advocate for a qualitative study to explore contextual factors influencing the knowledge of NCDs and access to healthcare services beyond the big domains of education and residence.